Influences of oxygen and temperature interaction on the antibacterial activity, antioxidant activity, serum biochemical indices, blood indices and growth performance of crucian carp - Wang, Bin; Mao, Hanping; Zhao, Jian; Liu, Yong; Wang, Yafei; Du, Xiaoxue (PeerJ, 2023)
The well-being of fish used in aquaculture is of great interest. Oxygen and temperature are the main factors affecting the welfare of the crucian carp (carassius); however, there are few studies on the combined effects of these on the species. Therefore, this study investigated the impact of different temperatures (18 °C, 24 °C, 30 °C) and oxygen concentrations (2.1 mgL−1, 5.4 mgL−1, 9.3 mgL−1) on serum antibacterial activity, antioxidant activity, hematological parameters and growth performance of the crucian carp. The results showed that there were greater antibacterial properties under conditions of hypoxia at 18 °C (L18) and hyperoxia at 24 °C (H24). The activities of catalase, glutathione peroxidase and total superoxide dismutase were the highest at 24 °C under hypoxia and hyperoxia. In addition, the contents of glucose and total protein first increased and then decreased with the change of temperature; triglycerides were the lowest at 30 °C. The blood parameters of the carp were within a normal range at 24 °C; however, the growth rate was at its lowest under hypoxia treatment at 30 °C (L30). This study showed that high temperature impairs the antibacterial ability, antioxidant capacity and growth performance of the crucian carp, and high oxygen levels can alleviate these adverse reactions. This research provides a theoretical basis for subsequent aquaculture studies.
Keywords: Environmental factors; Growth performance; Physiology; Biochemistry